DETERIORATION ANALYSIS OF STRUCTURAL AND FUNCTIONAL CONDITIONS OF POST-FLOOD FLEXIBLE PAVEMENT(CASE STUDY: JAYAPURA CITY BORDERLINE / KEEROM DISTRICT - ARSO, PAPUA) - Timang, Mitra
Pavement performance is the pavement’s ability to serve traffic loads and environmental influences according to the service life of the design plan. Basically, pavement performance deteriorates due to the cumulative effect of high traffic loads. However, flood-affected road segments tend to deteriorate faster in both structural and functional conditions because water can weaken the structural layer of the pavement, reduce the bearing capacity of the soil and increase surface damage such as roughness, ruttings and cracks. One of the pavement performance indicators that can be used to analyse the structural and functional condition of the pavement is based on the Remaining Life (RL). Indonesia has established the RL value as one of the Performance Programme Indicators (IKP) of Road Condition Rating to determine the urgency of damage and determine the type of maintenance in road preservation programme. In this research, the RL analysis uses 2 methods, which is the 1993 AASHTO Method with the consideration that in addition to the deflection data parameters from the LWD tool, this method also includes the subgrade bearing capacity as a support system for the pavement structure. Meanwhile, the RL analysis with Guideline No. 07/P/BM/2021 uses IRI data input according to the availability of existing data on the road segment under review. The analysis results show that there is deterioration both in the structural and functional condition of the pavement based on the RL value, with the highest deterioration shown by the structural condition of the pavement. This is because the structural condition calculates not only the strength of the pavement layers but also the bearing capacity of the subgrade, while the functional condition only describes the surface condition. With the difference in structural and functional RL values, there are also differences in maintenances type requirements. The decision on the maintenance’s type is based on the structural condition which is more severe than the functional condition of the pavement. However, the maintenance’s type determined based on structural conditions using the 1993 AASHTO Method is still optimal because in the decision-making chart, it begins with the IRI value which sufficiently represents the functional condition of the pavement.